The Impact of Acute and Chronic Exercise on Immunoglobulins and Cytokines in Elderly: Insights From a Critical Review of the Literature - Sellami, Maha; Bragazzi, Nicola Luigi; Aboghaba, Baha; Elrayess, Mohamed A. (Frontiers in Immunology, 2021)
The level of immunoglobulins and cytokines changes with an ageing immune system. This review summarizes findings from studies that have examined the impact of acute and chronic exercise on immunoglobulins and cytokines in the elderly. Our literature analysis revealed that acute endurance exercise resulted in increased secretory salivary immunoglobulin A (SIgA), while acute bouts of muscle strengthening exercise (i.e., isokinetic, eccentric, knee extensor exercise) increased plasma/muscle interleukin (IL)-6, IL-8 and tumor necrosis factor alpha (TNF-α) levels. Chronic exercise in the form of short-term endurance training (i.e., 12-16 weeks) and long-term combined endurance and resistance training (i.e., 6-12 months) induced increases in salivary SIgA concentration. We additionally identified that short-term endurance training at moderate intensities and the combination of endurance, strength, balance, and flexibility training increase plasma IL-10 and reduce plasma IL-6 and TNF-α in healthy elderly adults and male patients with chronic heart failure. Strength training for 6-12 weeks did not alter plasma IL-1β, IL-2, IL-6 and TNF-α concentration in healthy elderly adults and patients with chronic-degenerative diseases, while 12 weeks of resistance training decreased muscle TNF-α mRNA in frail elderly individuals. Short-term (i.e., 10-24 weeks) moderate- to high-intensity strength training reduced LPS–IL-6, LPS, IL-1β, LPS–TNF-α and circulating concentrations of TNF-α and increased IL-10 in healthy elderly women and older people with cognitive impairment, respectively. In conclusion, it appears that acute bouts of endurance exercise and short-term chronic exercise training exercise are appropriate methods to enhance mucosal immune function, reduce systemic markers of inflammation, and promote anti-inflammatory processes in elderly individuals.